'A Debt contracted in Italy': Ferdinando Tenducci in a London court and prison. (4th April 2014) - Duncan, Cheryll
Abstract: A legal case discovered in the National Archives in London illuminates the circumstances surrounding castrato Ferdinando Tenducci's imprisonment in 1760–61. His legal adversary, Francesco Giuliani, sought to recover damages sustained as a consequence of the non-payment of a debt that had accumulated over several years in Italy. Giuliani had apparently acted as manager/agent and perhaps teacher to the young Tenducci, and when the singer came of age in 1756 they entered into an agreement whereby Tenducci undertook to repay the debt in instalments. He failed to do so, and in 1758 moved to London where he probably expected to evade his creditor. Undeterred, Giuliani pursued him through the English legal system and Tenducci was summoned to court in February 1760; he failed to appear, and judgment was awarded against him. Unable to meet his liabilities or secure bail, the singer was committed to King's Bench Prison on 6 June but escaped three months later. The press announcement included a hitherto unnoticed description of the castrato's unusual physical characteristics; he was quickly recaptured, and remained in prison until 9 February. The case corrects a widespread misapprehension about the nature of Tenducci's indebtedness in 1760, sheds light on the contractual relationship between music agent and performer, and provides a rare example of litigation in which the venue in a dispute between two foreign nationals is relocated from Italy (where it originally lay) to England (where one of the parties resided).